Memory of Soviet Repressions in the Kazakhstan Lithuanian Diaspora: Interpretations, Practices, Contexts - Šutinienė, Irena (Genocidas ir rezistencija, 2024)
In this article, the focus is on the memory of repressions in the Kazakhstan Lithuanian diaspora, a large part of which consists of the descendants of Lithuanians who were subject to repression. Based on data from a survey of semi-structured interviews, the interpretations, evaluations, and practices for the memorialisation and commemoration of the memory of the repressions among the representatives of the diaspora are analysed. The connections of this memory with Kazakhstan’s dominant collective memory discourses and the Lithuanian narrative of the memory of repressions are discussed. The analysis reveals how discourses of the memory of the repressions in the country impact the memory of the descendant of the migrants.
Keywords: forced migration; memory of Soviet repressions; memory of migrant generations